Density Functional Theory Simulation of Structural, Electronic and Thermodynamic Properties of Nonylphenol Ethoxylate Surfactants - Jayalath, W.I.M.; Pandithavidana, D.R. (Sri Lanka Association for the Advancement of Science, Colombo 07, 2015)
‘Surfactants’ or ‘surface active agents’ are chemical agents capable of reducing the surface tension of a liquid in which it is dissolved. Nonylphenol ethoxylates (NPEs) are a group of non-ionic surfactants commonly known as Tergitol NP surfactants. Nonylphenol ethoxylates are classified according to the number of ethoxylate units in the hydrophilic chain. The properties of the nonylphenol ethoxylates differ with the number of ethoxylate units in the molecule. The hydrophilic-lipophilic-balance (HLB value) is the key parameter that surfactant formulators are focused on when studying the properties of non-ionic surfactants. Even though the HLB values of two surfactants are equal or close to each other, the expected properties cannot be obtained by replacing one surfactant with another. This issue leads to the necessity to carry out many trial and error tests to identify the equivalent surfactants in industrial applications. To address this issue, a comprehensive investigation of the nonylphenol ethoxylate molecules was carried out computationally at B3LYP level of theory using 6-311G basis set in Linux version of Gaussian 09 computer software package. The aqueous phase investigation focused on deducing the interactions between nonylphenol ethoxylates and water with extending chain length of the ethoxylate part, branching of the nonyl hydrocarbon chain and varying the substituent position (ortho-, meta- and para-) of nonylphenol ethoxylate molecules. To interpret the interactions of nonylphenol ethoxylate molecules with water, molecular properties such as Gibbs free energy changes of solvation (ΔGsolv) in aqueous medium, molecular dipole moments and hydrogen bond lengths between surfactant molecules and water molecules were investigated. The more negative values (-46.62 to -116.88 kJ/mol) of the Solvation Gibbs free energy (ΔGsolv) indicate that the stability of the NPEs in aqueous medium increases with the extension of the length of ethoxylate chain (4 to 16 ethoxylate units). The substituent position and the branching of nonyl-hydrocarbon chain have not caused the Gibbs free energy of solvation to change significantly. Although electrical dipole moment of NPEs in aqueous medium varied with the position of the substituents, it was not affected by branching patterns of the nonyl hydrocarbon group. Computationally simulated UV-Visible spectra of NPEs revealed that the absorption maximum of NPEs (λmax) was independent of ethoxylate chain length. UVVisible spectra generated from selected molecules of NPEs confirmed that absorption maximum (λmax) of the surfactant species was significantly affected by the change in position of substituents.